Abnormalities of structural covariance networks in drug-naïve boys with attention deficit hyperactivity disorder. Issue 3 (30th March 2015) - Li, Xinwei; Cao, Qingjiu; Pu, Fang; Li, Deyu; Fan, Yubo; An, Li; Wang, Peng; Wu, Zhaomin; Sun, Li; Li, Shuyu; Wang, Yufeng
Abstract: The aim of this study is to investigate whether the anatomical organization of large-scale brain systems would change in ADHD patients compared to healthy controls. We utilized a structural covariance network (SCN) mapping approach to investigate large-scale networks in 30 drug-naïve ADHD boys and 30 gender- and age-matched controls. The regions showing significant between-group differences in gray matter (GM) volume were defined as seed regions of interest. Then, the SCNs derived from these seeds were statistically compared between ADHD and controls. Significant regional GM volume decreases ( P <0.05, corrected) were observed in the right insula and the right orbito-frontal cortex (OFC) in ADHD relative to controls. Both SCNs derived from these two seeds showed more localized topology in ADHD group. Furthermore, significantly decreased structural connectivity were found between insula and right hippocampus, bilateral olfactory cortex, and between OFC and bilateral caudate nucleus ( P <0.05, corrected) in ADHD group. Significantly increased association was observed between insula and left middle temporal gyrus ( P <0.05, corrected) in ADHD group. Taken together, our results reveal abnormal regional brain anatomy as well as aberrant structural covariance networks in ADHD, supporting previous findings of dysfunction in distributed network organization in patients with ADHD. Highlights: Right insula and right orbito-frontal cortex showed significant GM volume reduction in ADHD. Both SCNs showed more localized topology in ADHD than controls. Simultaneous increases and decreases in structural connectivities in both SCNs.